Attention deficit/hyperactivity disorder and eating disorders: a brief review - Rodrigues, Márcia; Azevedo, Patrícia (BIRTH AND GROWTH MEDICAL JOURNAL, 2022)
Introduction: Attention deficit/hyperactivity disorder (ADHD) is a common neurodevelopmental disorder. The relationship between ADHD and eating disorders (EDs) has been recently often considered. Both conditions tend to have an early age of onset and can become chronic and persist into adulthood. Objective: This study aimed to elucidate the prevalence and overlap of ADHD and EDs and review the current evidence about an association between both conditions. It also sought to investigate some of the mechanisms potentially underlying these comorbid disorders. Methods: A brief review of the latest literature was performed on PubMed using the terms “attention deficit hyperactivity disorder”, “ADHD”, “eating disorders”, and “ADHD and ED”. Results: The prevalence of EDs in individuals with ADHD has been reported across a range up to 12 %. The literature describes an association between childhood ADHD and the development of EDs during adolescence. Conversely, ADHD symptoms have been reported in patients with EDs, more frequently in those with bulimia nervosa and anorexia nervosa purging subtype than with anorexia nervosa restrictive subtype. Impulsive behaviors constitute a core ADHD symptom and deficits in its regulation have been shown in patients with EDs. Conclusion: Evidence in the literature suggests an overlap between ADHD and EDs. More studies are required to retrieve additional insights into the clinical management of patients with both conditions.